PERANCANGAN WEB KOMIK “PEMBAWA CAHAYA” UNTUK MEMPERKENALKAN BUDAYA BATAK - Erlang Arsa Ridha Putra; Evelyne Henny Lukitasari; Yudi Wibowo (Canthing, 2024)
The design of the comic “Pembawa Cahya”t was motivated by the low quantity of Batak cultural web comics, especially in the action and fantasy genres. As for themes, there is a tendency to emphasize visual themes, such as traditional clothing or traditional houses, so that they don't really seem like the culture that exists in Indonesia today. This results in less interest in web comics with local themes. This design aims to make the audience more interested in local Indonesian cultural themes. Web comics were chosen because they area relevant entertainment medium in the millennial era where platforms and sites providing web comics have penetrated society. The story of The “Pembawa Cahaya” is designed so that the fantasy story wrapped in horror remains relevant by adding elements of kinship and cultural socialization in the local community. Most local web comics do not really raise social and cultural issues that are relevant to society, so they have few fans. Likewise, the issue of the harsh upbringing of sons from Batak families, even though there is a more fundamental reason for what actually happened, is rarely corrected in most Batak-themed story works. Using themes that are more local and relevant to society is aimed at reviving public interest in local web comics and can use web comics as a medium for promoting local cultures which is also an introduction to how the concept of culture actually applies, not just what the community interprets for themselves. Alone. This design uses observations in various fields, from provider platforms such as webtoon or comic toon as well as in data collection which is based on journals that are relevant to the theme raised. The design concept for this design is "Local culture in the modern era" whose concept is based on combining the concept of modernization with local culture that seems traditional.